Possible effect of climate change on the potential distribution of temperate forest tree species in Nuevo León, Mexico - Manzanilla-Quijada, Gyorgy Eduardo; Treviño-Garza, Eduardo Javier (Ecosistemas y Recursos Agropecuarios, 2024)
The global climate is changing significantly in recent years and with it the distribution of some species. The objective of this study was to estimate the impact of climate change on the potential distribution of 10 temperate forest tree species in the state of Nuevo León, Mexico, and to define conservation areas. The current and future potential distribution of each species was estimated from records and environmental variables, using 75% of the records to train and 25% to validate the models in the MaxEnt algorithm. The occupied surface of the study area was calculated and the percentage of reductions and increases under two scenarios (RCP4.5 and RCP8.5) of climate change was obtained. The results show AUC values above 0.900 for the training and validation data, however, the partial ROC tests showed values above 1.700, while the Z-analyses indicated excellent statistical performance (p
Keywords: Area reduction, conservation areas, forest species, forest management, MaxEnt.